STRATEGI PENCITRAAN PERUSAHAAN AGRIBISNIS MELALUI MEDIA VIRTUAL - Yusuf, Rinaldy; Purnaningsih, Ninuk (Sodality: Jurnal Sosiologi Pedesaan, 2010)
This study is about the effectiveness of agribusiness corporate brand image strategy which doing by PT. Plantera on virtual media and related factors. This study use quantitative approach with survey method and supported by qualitative data. Respondent is people who already visited Plantera Fruit Paradise Ngebruk’s fan page on Facebook and then decided to came to the Plantera. This study focused on relation between respondent’s social economic characteristics (gender, age, level education, and level income), public perception about the corporate, and corporate brand image strategy on Facebook Fan Page with the effectiveness itself. Based on result, from four social economic characteristics on respondent (gender, age, level education, level income) only level education, level income, and age of respondent that have relation with the effectiveness of corporate brand image strategy on Facebook Fan Page.. The conclusion of this study is the corporate brand image strategy which doing by PT. Plantera is well done and had an effective result on it’s implementation.